PENGUATAN FUNGSI LEGISLASI DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA MELALUI AMANDEMEN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Saputra, Randi; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The Regional Representative Council of the Republic of Indonesia is one of the state institutions established on the basis of reform. This institution is formed so that regional aspirations and interests within the state can be realized in advancing the state based on Pancasila. But in the 1945 Constitution of the Republic of Indonesia the regulation governing the authority of this legislative body is very limited, so far we understand one of the most important functions is the legislative function of this institution, but what happens if the arrangement in the country's own basis does not explain Functions against this institution. As in Article 22D Paragraphs (1) and (2) of the Regional Representative Council does not participate in the ratification of a draft Law, this is where the role of regional representatives is to preserve the aspirations of the region, even though Decision Number 92 / PUU-X / 2012 has been issued by The Supreme Court on the return of legislative function of DPD, still DPD does not arrive at approval stage in a decision making.Research methods in this research, first, the type of research is normative law and descriptive analysis. Both data sources are supported by primary, secondary and tertiary data sources. Third, the data collection technique used is literature study. After the collected data are analyzed in a qualitative way and draw conclusions with the method of thinking dedukti that is analyzing the problems of the general form of special form.From the results of this study there are two things that can be concluded, firstly, that the existence of the Regional Representative Council of the Republic of Indonesia in performing the function of limited legislation by the arrangement in the 1945 Constitution of the Republic of Indonesia on mutual agreement on the draft Law. Although there has been a decision of the Constitutional Court Number 92 / PUU-X / 2012 but it has not been able to fulfill the DPD legislation function against mutual agreement in the draft Law, because the judge only gives interpretation of the Law and not changes to the constitution. Secondly, it is understood that DPD is a representative institution of regions in Indonesia which have different interests at the national level and if not fulfilled the worst possibility of division, in this case it is expected to return the legislative function that is real to the Regional Representative Council by changing The articles contained in the body of the 1945 Constitution of the Republic of Indonesia in other words the strengthening of functions by way of Amendment of the Constitution of the Republic of Indonesia.Keywords: Strengthening Functions, Legislation, Regional Representative Council, Amendments, Laws.